Observations of Barren-Ground Caribou Travelling on Thin Ice during Autumn Migration - Miller, Frank L.; Gunn, Anne (ARCTIC, 1986)
In October 1982 we observed the consequences of migrating barren-ground (Rangifer tarandus groenlandicus) encountering lake ice too thin to bear their weight. The observations were made on a portion of taiga winter range of the Beverly caribou herd during autumn migration in the Northwest Territories. We observed caribou hesitating to cross ice that had no snow cover and also saw caribou breaking through ice. Bulls had greater difficulty extricating themselves from the ice water than did relatively light-bodied cows and young individuals. We necropsied one bull that we found dead after it had broken through the ice and remained in the water for more than 20 hours. The bull had died apparently from stress and hypothermia and had heavily traumatized areas on its forelegs and sternum from struggling to break the ice. We could not evaluate the overall extent of injuries and mortalities to caribou from their encounters with thin ice, although we observed signs that at least hundreds had broken through the ice on different lakes.Key words: behaviour, injuries, barren-ground caribou, Rangifer tarandus groenlandicus, thin ice, autumn migration, Northwest Territories Mots clés: comportement, blessures, caribou des landes, Rangifer tarandus groenlandicus, glace mince, migration automnale, Territoires du Nord-Ouest